Hole doping by pressure on the 1111 pnictides CaFeAsF and SrFeAsF - Freitas, Daniele C. (2014)
We determine the pressure phase diagram of the 1111 compounds CaFeAsF and SrFeAsF, up to 20 GPa and down to 4 K by electrical resistivity measurements and the change of structure up to 40 GPa at room temperature. The antiferromagnetic transition temperature, as determined by the derivative peak, shows a minimum at ~5 GPa (10 GPa) for the Ca (Sr) compound. For CaFeAsF, superconductivity appears at this minimum, coincident with the development of a previously reported monoclinic phase. For SrFeAsF, where the orthorhombic and the monoclinic phase were reported to coexist, superconductivity exists above P≥1 GPa. Both phase diagrams can be scaled by a shift of ~10 GPa pressure at which the volume of SrFeAsF and that of CaFeAsF at ambient pressure coincide. The difference of our phase diagram with that of electron-doped 1111 samples is accounted for by hole doping under pressure, which we verified through electron band structure calculations.